2007
DOI: 10.1080/10408410701364497
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Inactivation ofArcobacterspp., a Current Status and Future Prospect

Abstract: Arcobacter spp. has been isolated from food of animal origin (particularly meats) and from various kind of water. Despite its phylogenetically related neighbor Campylobacter, Arcobacter is regarded as an emerging foodborne pathogen. Since Arcobacter differs in its phenotypic characteristics, the physical and chemical treatments designed for elimination of campylobacters from food and environment needs to be verified. This review focuses on the occurrence, and mainly on susceptibility to various physical and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…In addition, the isolation method used in this work may have affected the species of Arcobacter detected, as most of the isolation methods used are not optimal for all Arcobacter species (28). The reported isolation of A. butzleri in industrial ricotta cheeses has significant food safety implications for the following reasons: (i) ricotta cheese is a ready-to-eat product, and Arcobacter-contaminated ricotta cheese could be considered a potential source of Arcobacter infection for consumers; (ii) ricotta cheese provides a substrate (pH Ͼ 6.0, water activity [a w ] of 0.98 to 0.99, and moisture content of 75 to 80%) that is not limiting for the survival of A. butzleri (32,33), as it is able to grow at a w values of 0.985 to 0.990 (34) and in the pH range of 6.0 to 8.0 (2); (iii) A. butzleri has been demonstrated to survive at refrigeration temperature in different substrates (8,35), including dairy products (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the isolation method used in this work may have affected the species of Arcobacter detected, as most of the isolation methods used are not optimal for all Arcobacter species (28). The reported isolation of A. butzleri in industrial ricotta cheeses has significant food safety implications for the following reasons: (i) ricotta cheese is a ready-to-eat product, and Arcobacter-contaminated ricotta cheese could be considered a potential source of Arcobacter infection for consumers; (ii) ricotta cheese provides a substrate (pH Ͼ 6.0, water activity [a w ] of 0.98 to 0.99, and moisture content of 75 to 80%) that is not limiting for the survival of A. butzleri (32,33), as it is able to grow at a w values of 0.985 to 0.990 (34) and in the pH range of 6.0 to 8.0 (2); (iii) A. butzleri has been demonstrated to survive at refrigeration temperature in different substrates (8,35), including dairy products (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of A. butzleri to tolerate chlorine concentrations close to working solutions used for sanitizing in food processing plants was recently reported (36). Further, the ability of this species to form biofilms (34) or to incorporate in a preestablished biofilm as a secondary colonizer (9), together with its ability to proliferate at chiller temperatures (34), suggests that A. butzleri can colonize and multiply in parts of the processing surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…All these outbreaks were related to the presence of fecal contamination, but the capacity of Arcobacter to adhere to different types of pipes and to form biofilms (8) should be considered. Although the susceptibility of A. butzleri to chlorine has been demonstrated (20,112,129), it was not known if conventional procedures for drinking water treatment could effectively remove this bacterium, as described by Ho et al (64). In a recent study it was found that although the species A. butzleri and A. cryaerophilus were very prevalent in the Llobregat River water (one of the main sources of drinking water production for the metropolitan area of Barcelona, Spain), these species were never detected or isolated from finished drinking water, clearly demonstrating that water treatment is effective in removing Arcobacter species (27).…”
Section: Arcobacter In Watermentioning
confidence: 99%
“…The loss of culturability of this species in nonchlorinated water stored at 12°C occurs after 21 days (112), while according to other authors, it occurs after 3 to 4 weeks on agar plates at 4°C (20). Moreover, it has been reported that A. butzleri has the ability to become viable but nonculturable (VBNC) when subjected to different laboratory conditions (20,45), but this VBNC state has not yet been shown to occur in Arcobacter in natural aquatic environments.…”
Section: Arcobacter In Watermentioning
confidence: 99%
See 1 more Smart Citation